The Influence of Live Streaming and Online Reviews on Purchase Intention Toward Luxcrime on TikTok Shop: The Mediating Role of Customer Trust - Rahmi, Via Aulia; Firman, Firman (Journal of Management and Administration Provision, 2025)
Technological advancements have changed how customers use e-commerce platforms to engage with products.  Live streaming is one of the most popular features, and it may affect consumers' intentions to make purchases.  With consumer trust acting as a mediating variable, this study intends to examine how live broadcasting and online customer reviews affect consumers' intentions to buy Luxcrime products on TikTok Shop.  This study employs a quantitative methodology, gathering primary data from 275 respondents via an online survey using purposive sampling.  With the help of the SmartPLS program, structural equation modeling, or SEM, was used to analyze the data.  The study's findings showed that consumer trust and purchasing intention are positively and significantly impacted by live broadcasting and online customer reviews.  Additionally, it was shown that the relationship between live streaming, online customer reviews, and buy intention was mediated by consumer trust.  Through the use of live streaming features and efficient customer review management on e-commerce platforms, these findings emphasize the significance of establishing consumer trust in order to increase buy intention.